Testing the environmental Kuznets curve hypothesis: the role of energy consumption and democratic accountability - Gungor, Hasan; Olanipekun, Ifedolapo Olabisi; Usman, Ojonugwa (Springer Heidelberg, 2021)
Considering the role democratic structures play in shaping the policies that enhance environmental quality, this paper tests the environmental Kuznets curve (EKC) hypothesis by incorporating the role of energy consumption and democratic accountability for nine countries between 1990 and 2014. The pooled mean group (PMG) methodology and Emirmahmutoglu-Kose Granger causality test are employed. The empirical results validate the EKC hypothesis in the long run. The results also confirm that energy consumption significantly increases CO(2)emissions in the long run and short run, while democratic accountability significantly reduces CO(2)emissions in the long run. Causality test results indicate a two-way causal relationship between democratic accountability and economic growth, and also between energy consumption and economic growth. The study recommends among others, the need to strengthen democratic accountability and improve access to information that protects the environment.
Keywords: CO(2)emissions; Energy consumption; Democratic accountability; Panel data; PMG model